CLINICAL SIGNIFICANCE OF Toll2, Toll4, CD14, AND HLA-DR EXPRESSION ON THE MONOCYTES IN PATIENTS WITH SEPSIS - V. A. Lazanovich; E. V. Markelova; G. A. Smirnov; T. P. Smolina (Медицинская иммунология)
Expression of Toll-like receptors (TLRs) on myeloid cells is of key importance for induction of systemic reactions caused by bacterial damage, and activation mechanisms of innate immune response. The study included thirty-six patients with sepsis in whom we assessed a prognostic value of TLR2, TLR4, CD14, HLA-DR expressed on monocytes, depending on severity of the disease and clinical outcomes. There were neither significant differences in TLR4 expression at all stages of clinical observation, nor correlations between expression of this marker on monocytes and severity of the disease, or outcomes of septic conditions. Low levels of MFI on monocytes TLR2, HLA-DR at 5 and 10 days, like as decreased expression of CD14 on 10th day of the disease were shown to be predictive for poor clinical outcomes of sepsis.